Effect of exercise referral schemes upon health and well-being: initial observational insights using individual patient data meta-analysis from the National Referral Database. Issue 1 (18th November 2019) - Wade, Matthew; Mann, Steven; Copeland, Rob J; Steele, James
Abstract : Objectives: To examine if exercise referral schemes (ERSs) are associated with meaningful changes in health and well-being in a large cohort of individuals throughout England, Scotland, and Wales from the National Referral Database. Methods: Data were obtained from 23 731 participants from 13 different ERSs lasting 6 weeks to 3 months. Changes from pre- to post-ERS in health and well-being outcomes were examined including body mass index (BMI), blood pressure (systolic (SBP) and diastolic (DBP)), resting heart rate (RHR), short Warwick Edinburgh Mental Wellbeing Scale (SWEMWBS), WHO Well-Being Index (WHO-5), Exercise Related Quality of Life scale (ERQoL), and Exercise Self-Efficacy Scale (ESES). Two-stage individual patient data meta-analysis was used to generate effect estimates. Results: Estimates (95% CIs) revealed statistically significant changes occurred compared with point nulls for BMI (−0.55 kg.m 2 (−0.69 to −0.41)), SBP (−2.95 mmHg (−3.97 to −1.92)), SWEMWBS (2.99 pts (1.61 to 4.36)), WHO-5 (8.78 pts (6.84 to 10.63)), ERQoL (15.26 pts (4.71 to 25.82)), and ESES (2.58 pts (1.76 to 3.40)), but not RHR (0.22 f c (−1.57 to 1.12)) or DBP (−0.93 mmHg (−1.51 to −0.35)). However, comparisons of estimates (95% CIs) against null intervals suggested the majority of outcomes may not improve meaningfully. Conclusions: We considered whether meaningful health and well-being changes occur in people who are undergoing ERSs. These results demonstrate that, although many health and well-being outcomes improved, the changes did not achieve meaningful levels. This suggests the need to consider the implementation of ERSs more critically to discern how to maximise their effectiveness.